PLGA-Based Nanoparticles in Cancer Treatment - Rezvantalab, Sima; Drude, Natascha Ingrid; Moraveji, Mostafa Keshavarz; Güvener, Nihan; Koons, Emily Kate; Shi, Yang; Lammers, Twan; Kiessling, Fabian (Frontiers in Pharmacology, 2018)
Nanomedicines can be used for a variety of cancer therapies including tumor-targeted drug delivery, hyperthermia, and photodynamic therapy. Poly (lactic-co-glycolic acid) (PLGA)-based materials are frequently used in such setups. This review article gives an overview of the properties of previously reported PLGA nanoparticles (NPs), their behavior in biological systems, and their use for cancer therapy. Strategies are emphasized to target PLGA NPs to the tumor site passively and actively. Furthermore, combination therapies are introduced that enhance the accumulation of NPs and, thereby, their therapeutic efficacy. In this context, the huge number of reports on PLGA NPs used as drug delivery systems in cancer treatment highlight the potential of PLGA NPs as drug carriers for cancer therapeutics and encourage further translational research.